2011
DOI: 10.1523/jneurosci.6542-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Presynapses in Kenyon Cell Dendrites in the Mushroom Body Calyx of Drosophila

Abstract: Plastic changes at the presynaptic sites of the mushroom body (MB) principal neurons called Kenyon cells (KCs) are considered to represent a neuronal substrate underlying olfactory learning and memory. It is generally believed that presynaptic and postsynaptic sites of KCs are spatially segregated. In the MB calyx, KCs receive olfactory input from projection neurons (PNs) on their dendrites. Their presynaptic sites, however, are thought to be restricted to the axonal projections within the MB lobes. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 85 publications
3
92
0
Order By: Relevance
“…We also demonstrate reconstitution of GFP between Kenyon cells and the Odd neurons. Presynaptic densities have been observed in the Kenyon cell dendrites (Christiansen et al, 2011), and, while the extent of labeling between Kenyon cells and the Odd neurons is less extensive than that seen between the Odd neurons and PNs, it suggests that the Odd neurons are connected with Kenyon cells. In that case, these connections must be dendro-dendritic synapses, and, as such, it is not possible to infer directionality from the GRASP studies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We also demonstrate reconstitution of GFP between Kenyon cells and the Odd neurons. Presynaptic densities have been observed in the Kenyon cell dendrites (Christiansen et al, 2011), and, while the extent of labeling between Kenyon cells and the Odd neurons is less extensive than that seen between the Odd neurons and PNs, it suggests that the Odd neurons are connected with Kenyon cells. In that case, these connections must be dendro-dendritic synapses, and, as such, it is not possible to infer directionality from the GRASP studies.…”
Section: Discussionmentioning
confidence: 91%
“…For the Mosaic Analysis with a Repressible Cell Marker (MARCM) clones, we used, in addition to the Odd-Gal4 line, FRT 19A,and FRT19A,, and Dynein mutant (Zheng et al, 2008). GFP reconstruction across synaptic partners (GRASP) was performed using, in combination with the Odd-Gal4 driver, GH146-LexA-GAD (Sudhakaran et al, 2012), MB247-LexA-VP16 (Burke et al, 2012), UAS-CD4::spGFP1-10, and LexAop-CD4::spGFP11 (Kreher et al, 2008). For functional imaging UAS-GCaMP6(fast) (Bloomington Stock Center; Akerboom et al, 2012) was driven using the Odd-Gal4 line.…”
Section: Methodsmentioning
confidence: 99%
“…To understand how color information is processed in the deep visual centers, we set out to identify the synaptic targets of these chromatic Tm neurons. First, we used the ort C1a -LexAVP16 driver to express an active-zone marker, Brp D3 ::mCherry, in all four types of Tm neurons, to mark their presynaptic sites (Christiansen et al, 2011;Karuppudurai et al, 2014;Ting et al, 2014;Melnattur et al, 2014). We found that the presynaptic sites of these neurons were localized to the axon terminals in the deep lobula strata, Lo4-6 (Fischbach and Dittrich, 1989; Figure 1B1), as well as their dendrites in the medulla (stratum M8; Figure 1B).…”
Section: Four Types Of Chromatic Tm Neurons Are Presynaptic In the Lomentioning
confidence: 99%
“…It is possible that there may be some communication between g lobe neurons and a/b lobe neurons before or during memory retrieval. This communication can be mediated by MB intrinsic neurons and extrinsic neurons (Krashes et al 2007;Lee et al 2011;Qin et al 2012), or achieved by direct interaction (Christiansen et al 2011).…”
Section: Olfactory Early Memories: From Formation To Retrievalmentioning
confidence: 99%